Does Drawing Down the U.S. Strategic Petroleum Reserve Help Stabilize Oil Prices? - Lutz Kilian; Xiaoqin Zhou (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the efficacy of releases from the U.S. Strategic Petroleum Reserve (SPR) within the context of fully specified models of the global oil market that explicitly allow for storage demand as well as unanticipated changes in the SPR. Using novel identifying strategies and evaluation methods, we examine seven questions. First, how much have exogenous shocks to the SPR contributed to the variability in the real price of oil? Second, how much would a one-time exogenous reduction in the SPR lower the real price of oil? Third, are exogenous SPR releases partially or fully offset by increases in private sector oil inventories and how does this response affect the transmission of SPR policy shocks? Fourth, how effective were actual SPR policy interventions, consisting of sequences of exogenous changes in the SPR, at lowering the real price of oil? Fifth, are there differences in the effectiveness of SPR emergency drawdowns and SPR exchanges? Sixth, how much did the creation and expansion of the SPR contribute to higher real oil prices? Finally, how much would selling half of the oil in the SPR, as recently proposed by the White House, lower the global price of oil (and hence the U.S. price of motor gasoline) and how much fiscal revenue would it generate.
Keywords: Q38; Q43; E62; 330; SPR; crude oil; oil inventories; storage; expectations; policy intervention; fiscal policy